2016
DOI: 10.1080/15627020.2016.1145071
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of adrenocortical activity in a myrmecophageous mammal, the bat-eared fox

Abstract: Measuring physiological stress reactions through the quantification of plasma cortisol often involves physically restraint, which acts as a stressor itself.Here, we present the validation of a non-invasive method for assessing adrenocortical activity as an indicator of stress in the bat-eared fox (Otocyon megalotis). By conducting an adrenocorticotropic hormone (ACTH) challenge, we examined the suitability of three enzyme immunoassays (EIAs) detecting 11,17 dioxoandrostanes (11,17-DOA) as well as faecal glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(14 reference statements)
2
7
0
Order By: Relevance
“…This lack of relationship with social behaviour is likely attributable to relatively low rates of negative social interactions in foxes. Faecal glucocorticoid metabolite levels in foxes peak between 24 and 48 h after experiencing stress (le Roux et al ., ). It is possible due to our sampling procedure that periods of elevated fGCM levels were missed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This lack of relationship with social behaviour is likely attributable to relatively low rates of negative social interactions in foxes. Faecal glucocorticoid metabolite levels in foxes peak between 24 and 48 h after experiencing stress (le Roux et al ., ). It is possible due to our sampling procedure that periods of elevated fGCM levels were missed.…”
Section: Discussionmentioning
confidence: 97%
“…At the ERL, we prepared faecal samples and extracted the hormone metabolites as previously described by le Roux et al . (). Following freeze‐drying, faecal samples were pulverized before 0.05–0.06 g of faecal powder was weighed out.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, European starlings ( Sturnus vulgaris ) exposed to chronic stressors downregulate corticosterone secretion to avoid the negative effects on glucose production and immune function (Cyr et al ). Few researchers have studied glucocorticoid production in small canids (Nelson et al , Le Roux et al ), and more data are needed to understand the relationship between GC production and environmental stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that veterinary examinations, including sedation, can cause both physiological, and behavioral stress in captive and zoo‐housed animals (Heistermann et al, ; Waiblinger, Menke, Korff, & Bucher, ). Illness, injury, and related treatment have also been known to elevate fGCM concentrations (Ganswindt et al, ; Heistermann et al, ; LeRoux, Botha, Dalerum, & Ganswindt, ). Notably, golden langur Zoo 3 had the highest concentrations of fGCM of our five individually monitored captive animals.…”
Section: Discussionmentioning
confidence: 99%